2023
DOI: 10.1002/14651858.cd012849.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for management of functional abdominal pain disorders in children

Abstract: The primary objectives are to evaluate the efficacy and safety of probiotics for the management of IBS, abdominal migraine and functional abdominal pain in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
0
1
0
1
Order By: Relevance
“…Вважаєть ся доцільним рекомендувати пацієнтам, які бажають спробувати пробіотики, приймати їх на термін до 12 тижнів і припинити прийом, якщо не спостерігається поліпшення симптомів (рекомендація: слабка, якість доказів: дуже низька). У дітей існують інші докази ефективності застосування пробіотичної терапії: не щодавно опублікований кокрейнівський огляд оцінив ефективність і безпеку пробіотиків у дітей з функ ціональним болем [46], і метааналіз продемонстру вав докази середньої та високої якості ефективності Lactobacillus rhamnosus GG і Lactobacillus reuteri DSM в успішному лікуванні СПК у дітей. Про використання цих штамів ідеться й у рекомендаціях Робочої групи ESPGHAN від 2023 року [41].…”
Section: ë³êàðþ ùî ïðàêòèêóº / Practicing Physicianunclassified
“…Вважаєть ся доцільним рекомендувати пацієнтам, які бажають спробувати пробіотики, приймати їх на термін до 12 тижнів і припинити прийом, якщо не спостерігається поліпшення симптомів (рекомендація: слабка, якість доказів: дуже низька). У дітей існують інші докази ефективності застосування пробіотичної терапії: не щодавно опублікований кокрейнівський огляд оцінив ефективність і безпеку пробіотиків у дітей з функ ціональним болем [46], і метааналіз продемонстру вав докази середньої та високої якості ефективності Lactobacillus rhamnosus GG і Lactobacillus reuteri DSM в успішному лікуванні СПК у дітей. Про використання цих штамів ідеться й у рекомендаціях Робочої групи ESPGHAN від 2023 року [41].…”
Section: ë³êàðþ ùî ïðàêòèêóº / Practicing Physicianunclassified
“…Several preceding systematic reviews, including a Cochrane review by Wallace et al [18], revealed the positive effects of probiotics and synbiotics on functional abdominal pain disorders, confirming that probiotics and synbiotics (as a class of drugs) may be beneficial in alleviating GI symptoms among children, but the evidence is of low certainty. Probiotics may achieve more treatment success when compared with placebo at the end of the treatment, with 50% success in the probiotic group vs. 33% success in the placebo group (RR 1.57, 95% CI: 1.05-2.36; 554 participants; 6 studies; I2 = 70%; low-certainty evidence).…”
Section: Agreement and Disagreement With Other Studies Or Reviewsmentioning
confidence: 99%